Pendidikan Remaja Perspektif Al-Qur’an: Kajian Tematik Surah Yusuf dan Al-Kahfi - Hidayat, Muhammad Taufik (TSAQOFAH, 2026)
Adolescent education plays an important role in shaping character and personality in accordance with Islamic values, especially in facing the challenges of modern life. This study aims to explore the values of adolescent education contained in Surah Yusuf and Surah Al-Kahf and to identify their relevance to the dynamics of contemporary adolescent life. This study used a thematic (maudhū‘ī) approach through the steps of tafsir analysis to understand relevant verses, supported by library research from classical and contemporary tafsir. The results showed that Surah Yusuf contains educational values concerning patience, firmness of faith, and self-control in facing temptation. Meanwhile, Surah Al-Kahf emphasizes the importance of piety, wisdom, and good friendship as moral safeguards for adolescents. These findings confirm that adolescent education from the perspective of the Qur’an, as reflected in Surah Yusuf and Surah Al-Kahf, has strong relevance in shaping individuals with noble character who are able to face the dynamics of life. The contribution of this study lies in strengthening the concept of Islamic values-based adolescent education through thematic tafsir studies.